Assessment of Digital Marketing Management in Companies - T. D. Kolodnik (Цифровая трансформация)
An assessment of digital marketing management in the work of companies was carried out – namely, the compliance of internal resources with the mechanisms of digital transformation in marketing. The approach to the digital transformation of marketing systems and the principles of digital marketing management are considered. It is noted that digital marketing management is inseparable from the continuous process of developing the functions of the marketing system. The stages are proposed, on the basis of which a methodology for calculating the marketing management index in the work of companies is developed in order to analyze the digital marketing methods. It is proposed to divide the performance indicators of digital marketing communications into strategic, analytical and operational, and combine them into the classes in accordance with the methods. Based on the results of the assessment of digital marketing management, it is concluded that the theoretical basis for the economic success of many companies is the professional flexibility of top management specialists and marketing departments.